PATTERNS OF TEACHER – STUDENTS INTERACTION A Case Study of Classroom Interaction in Eleventh Grade of Senior High School in Cimahi - Anisah Rizkiani Amin (Journal of English and Education, 2015)
This paper presents the results of an investigation of teacher –students interaction (classroom interaction) patterns and the influence of Teacher Talk  to the classroom interaction patterns in Eleventh grade of Senior High School in Cimahi. The data were analyzed by using Suherdi’s (2010) framework as a part of classroom discourse analysis (CLDA) and Foreign Language Interaction Analysis (FLINT) system as proposed by Moskowitz (1971). The findings show that there are various types of classroom interaction patterns occur in the classroom. From those various patterns, simple non –anomalous K1 –initiated patterns dominate the interaction between teacher and students in the classroom. Whereas, the dominant categories of Teacher Talk are giving information and asking questions. Moreover, the occurance of classroom interaction patterns are related to the dominance of Teacher Talk which includes the types of questions given during the lesson.